Kedudukan Pembagian Hak Bersama Waris Sebagai Peralihan Harta Yang Dibebaskan Pajak Penghasilan - Bayu Indra Permana; Dominikus Rato; Dyah Octhorina Susanti (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
The transfer of property to certain heirs for the joint ownership of the object of inheritance must be transferred by way of the distribution of joint rights, which is based on the APHB. Article 4 paragraph (3) letter b of the Income Tax Law explains that the transfer due to inheritance is exempt from collecting PPh, but in its implementation it must be accompanied by a PPh SKB issued by KPP Pratama. So that in order to get the income tax exemption on the transition, the heirs must apply for the issuance of the SKB PPh to the KPP Pratama. However, the KPP Pratama often refuses the issuance of the SKB PPh, this results in the heirs having to pay PPh on the transition. This study uses a normative juridical method with a statutory approach and a conceptual approach, and legal materials are analyzed using a deductive method. The results of this study indicate that the transfer of land rights by the distribution of joint rights of inheritance should be exempted from income tax, because the distribution of joint rights is still included in the series of inheritance processes, so the transfer of income tax collection must be exempted. So that legal reform is needed to provide legal certainty in the exemption of PPh on the transition. Keywords: Standing, Distribution of Inheritance, Income Tax, Transfer of Land Rights